Efficiency Of Land Transport Connectivity In Relation To Port Tariff Structure In Batu Ampar - Prasetyo, Hans Blix; Syihabuddin, Achmad Syahmi; Maulana, Muhammad Hafizh; Putra, Septio Pratama; Ranggana Putra, Mhd Rayhan (Journal of Collaborative Industrial Management (JCIM), 2025)
Batu Ampar Port, as the main logistics gateway in Batam Island, plays a critical role in Indonesia's national supply chain, particularly in handling export-import containers. Despite its strategic location within a Free Trade Zone (FTZ), the port faces challenges in ground transportation connectivity due to low tariffs, limited internal infrastructure, incomplete digital integration, and high truck idle times. This study analyzes the impact of port tariffs regulated under PERKA BP Batam No. 4/2023 on operational efficiency, using field data from private trucking operators and Persero-managed operations. Comparative analysis with Tanjung Priok, Tanjung Perak, and Singapore Port highlights gaps in tariff structure, system integration, and throughput. Results indicate that low tariffs, while enhancing cost competitiveness, constrain investment in modern equipment and digital systems, leading to congestion and delayed container distribution. Based on these findings, short-term strategies such as dynamic tariff implementation, mandatory vendor integration into digital systems, and training are proposed. Long-term recommendations include separation of domestic and international traffic flows, development of real-time logistics dashboards, and periodic tariff revision. Implementing these strategies is expected to enhance operational efficiency, reduce idle times, and ensure sustainable port operations.